Determination of dynamic load features of tank containers when transported by rail ferry - Fomin, Oleksij; Lovska, Alyona; Melnychenko, Olexandr; Shpylovyi, Ivan; Masliyev, Vyacheslav; Bambura, Olga; Klymenko, Maryna (Eastern-European Journal of Enterprise Technologies, 2019)
Simulation of the dynamic load of the tank container when transported as part of a combined train on a rail ferry is carried out. Mathematical models taking into account possible interactions of tank containers with the frame of flat cars are developed. Calculations are made for the tank container of 1CS type size placed on the 13-4012M flat car. It is taken into account that the transportation of the tank container is carried out on the “Geroi Shipki” type rail ferry by the Black Sea. It is found that the greatest acceleration acts on the tank container in case of displacement of the flat car relative to the deck and the tank container relative to the frame. The total value of acceleration is about 0.9g. The stability of the tank container when transported by rail ferry is investigated. Permissible roll angles of the rail ferry that ensure the stability of the tank container relative to the flat car frame are calculated. Computer simulation of the dynamic load of the tank container when transported by rail ferry is carried out. The calculation is made in the CosmosWorks software environment. The fields and numerical values of the accelerations acting on the tank container are determined. The developed models are verified by the F-criterion. The research will help to provide safety and to make recommendations on sea transportation of combined trains by rail ferries, as well as to design tank containers with improved technical-economic, strength and environmental characteristics.